Methylation of the ESR1 CpG island in the colorectal mucosa is an 'all or nothing' process in healthy human colon, and is accelerated by dietary folate supplementation in the mouse. (1st August 2005) - Belshaw, N.J.; Elliott, G.O.; Williams, E.A.; Mathers, J.C.; Buckley, L.; Bahari, B.; Johnson, I.T.
Abstract : ESR1 is frequently silenced by CGI (CpG island) methylation, both in human colorectal tumours and, in an age-dependent manner, in healthy mucosa. It is not clear, however, whether methylation of individual cytosines occurs randomly within the epithelial genome, or preferentially within individual cells as an 'all-or-nothing' phenomenon. CGI methylation can be quantified in human DNA residues recovered from faecal samples. We used bisulphite genomic sequencing of human DNA from this source and from a colorectal cancer cell line (SW48) to show that the ESR1 CGI is methylated in an allele-specific manner. This provides support for the 'all or none' mechanism for methylation of this gene, and shows how age-dependent methylation of the ESR1 CGI leads rapidly to silencing of the gene within the cells, and hence the colonic crypt within which it occurs. Preliminary studies with a rodent model suggest the rate of age-dependent methylation of ESR1 is modifiable by dietary folate.